Navigating Spheno-Orbital Meningioma in Indonesia: Clinical Characteristics and Diagnostic Considerations from a Decade of Experience - Sumargo, Sheila; Guata Naibaho; Roland Sidabutar (HM Publisher, 2025)
Background: Spheno-orbital meningiomas (SOM) represent a distinct subgroup of meningiomas originating from the sphenoid wing, characterized by orbital extension, significant bony invasion, and hyperostosis. These tumors present diagnostic and therapeutic challenges due to their complex anatomical location near critical neurovascular structures and a notable tendency for recurrence. Understanding the specific clinical profile of SOM patients is essential for timely diagnosis and effective management strategies. This study aimed to delineate these characteristics within an Indonesian population. Methods: A retrospective, descriptive, cross-sectional study was performed using medical record data from patients diagnosed with SOM between January 2012 and December 2022 at the Department of Neurosurgery, Dr. Hasan Sadikin General Hospital, Bandung, Indonesia. Data collected included patient demographics, case history (new vs. recurrent), presenting symptoms, neurological status (Glasgow Coma Scale), and radiological findings (lesion singularity/multiplicity). Total sampling was employed, and data were analyzed descriptively. Results: The study included 252 subjects. A striking female predominance was observed (95.6%), with a mean patient age of 44.3 years (range 14-79). The vast majority were new cases (94.4%). Protrusion (proptosis) was the most frequent presenting symptom (79.0%), followed by headache (11.1%), blindness (5.2%), and blurred vision (4.0%). Most patients (97.2%) were fully conscious (GCS 15) upon admission. Radiological assessment revealed single lesions in 71.4% of cases. Conclusion: In this large Indonesian cohort, SOM predominantly affected middle-aged females and typically presented with proptosis. Awareness of this distinct clinical signature is crucial for improving diagnostic accuracy and facilitating prompt, comprehensive management. The findings underscore the need for high clinical suspicion, particularly in female patients presenting with orbital symptoms.